Comparing the Effects of Twice-Daily Exenatide and Insulin on Renal Function in Patients with Type 2 Diabetes Mellitus: Secondary Analysis of a Randomized Controlled Trial. (October 2022) - Zhang, Jie; Xian, Tong-Zhang; Wu, Ming-Xiao; Li, Chen; Wang, Weihao; Man, Fuli; Zhang, Xianbo; Wang, Xiaoxia; Pan, Qi; Guo, Lixin
This is a secondary analysis of a randomized controlled trial (RCT) on the effects of the glucagon-like peptide-1 receptor agonists exenatide and insulin aspartate 30 injection on carotid intima-media thickness. Here, we report the renal outcomes of the intervention in patients with type 2 diabetes mellitus (T2DM). Data from the RCT study was used to evaluate the effect of exenatide or insulin given for 52 weeks on estimated glomerular filtration rate (eGFR) in patients with T2DM. The primary end point was the change in the eGFR from baseline between the exenatide and insulin groups in normal versus overweight patients and patients with obesity. The secondary end point was the correlation between change in eGFR and oxidative stress, glycemic control, and dyslipidemia. There was a significant difference in eGFR between the insulin and exenatide groups at 52 weeks (p=0.0135). Within the insulin group, the eGFR remained below baseline at 52 weeks in all patients, and there was an increase in body weight in the normal group compared with the overweight patients and patients with obesity. The opposite was observed in the exenatide group. A decrease in body weight was prominent in the exenatide group at 52 weeks (p<0.05), the eGFR was below baseline in overweight patients and patients with obesity and significantly above baseline in the normal group (p<0.05). The eGFR was positively correlated to 8-oxo-7, 8-dihydroguanosine in the insulin group (p<0.05) but not the exenatide group. It can be concluded that compared with insulin, exenatide may improve renal function in overweight patients and patients with obesity more than in normal-weight patients with T2DM, but a further RCT is needed to confirm this effect.